Parent post-traumatic growth after a child's critical illness - Lauren M. Yagiela; Lauren M. Yagiela; Camera M. Edgar; Felicity W. K. Harper; Kathleen L. Meert; Kathleen L. Meert (Frontiers Media S.A., 2022)
ObjectivePost-traumatic growth is the experience of a positive change after a traumatic event. Our objective is to characterize the factors associated with post-traumatic growth in parents after a child's pediatric intensive care unit (PICU) admission.Study designA cross-sectional survey study examining post-traumatic growth and select independent variables in parents 1 year after a child's ≥72 h PICU admission for an acute illness or injury. The study was completed in parents of children discharge alive from a tertiary care PICU from January 1, 2017 to December 31, 2017. A mixed-effects linear regression model was built to evaluate the association of post-traumatic stress, anxiety, depression, resiliency, family function, and child function with post-traumatic growth.ResultsEighty-two parents of 52 children discharged alive in 2017 completed the survey. Fifty-two percent were ≥35 years and 64.3% were mothers. Median age of their children was 2.8 years (IQR 0.5-11.3) with a median hospital stay of 12 Days (IQR 6-20). Moderate-to-high levels of post-traumatic growth occurred in 67.1% of parents. Increased hospital length of stay (β Coeff 0.85; p = 0.004, 95% CI 0.27, 1.43) and parent post-traumatic stress symptoms (β Coeff 1.04; p = 0.006, 95% CI 0.29, 1.78) were associated with increased post-traumatic growth, and increased parent depression symptoms (β Coeff −1.96; p = 0.015; 95% CI −3.54, −0.38) with decreased post-traumatic growth.ConclusionLonger child hospital stays and increased parent post-traumatic stress symptoms were associated with increased post-traumatic growth, while increased depression was associated with less post-traumatic growth. The impact of future PICU parent psychosocial interventions on parents may be best assessed using a dual outcome focused on both reducing negative mental health symptoms while concurrently promoting skills to facilitate parent adaptation and post-traumatic growth.